Poverty and inequality in remote upland areas in Walapane: spatial patterns and Geographic determinants - Senanayake, S.G.N.C.; Perera, U.T.G.; Egodage, D.L.N. (University of Colombo, 2018)
Poverty is a complex and multidimensional social phenomenon. It is widespread and includes a broad, Worldwide population, from children to the elderly, and not excluding ethnic minorities. Poverty in Sri Lanka continues to be a large problem. Sri Lanka's life expectancy and literacy rate are nearly on par With those of developed countries, and even top the rankings for the South Asia region. While all these indicate that Sri Lanka should be experiencing a high standard of living, until recently it has only ranked in the medium category of the Human Development Index (HDI). However, still there are significant disparities across sectors, provinces and districts. Poverty is high in the rural sector and low in the urban sector. Rural poverty has received less attention than urban poverty from both policymakers and researchers. This study was conducted in two Grama Niladhari Divisions (GN) in Walapane Divisional secretariat which situated in the high elevation range with more than 3000 feet above the sea level The main objectives of the study is to identify the income diversification of the area and recognize the spatial distribution of poverty in the region. Data were collected in Roopaha and Alakolawewa areas using stratified sampling method which represent the all elevation levels in the region. Poverty head count Index and poverty gap index were developed in order to value the poverty in the study area. Further, the official poverty line of Nuwara eliya has been used to identify the poverty levels of the region. The analysis confirms that the inequality in per capita income is relatively low in both GN by local standards. Both Poverty headcount index and poverty gap index reveals an equal poverty level in Both GN divisions. The spatial patterns in income diversification emphasize that income and elevation are inversely correlated in both GN Divisions. Trend analysis demonstrate the spatial variation of poverty directions within the GN divisions. Findings indicate the need for new directions in future poverty research and a reconsideration of the importance of space in poverty theories.
Keywords: Poverty; Income; Elevation; Walapane